SERVICE QUALITY AND RELIGIOSITY AS DETERMINANTS OF SAVING DECISIONS IN ISLAMIC MICROFINANCE INSTITUTIONS - Roy Mabruri; Finny Ligery; Agus Setiawan (Program Studi Ekonomi Syariah, Universitas Pangeran Diponegoro Nganjuk, 2026)
This study aims to examine the role of service quality and religiosity as determinants of members’ saving decisions in Islamic microfinance institutions. This research employs a quantitative approach with an explanatory design. Data were collected through questionnaires distributed to 77 members of an Islamic microfinance institution and analyzed using multiple linear regression. The results indicate that both service quality and religiosity have a positive and significant effect on members’ saving decisions, both partially and simultaneously. Religiosity is found to have a more dominant contribution compared to service quality. Simultaneously, the two variables explain 74.1% of the variance in saving decisions. These findings suggest that improving service quality alongside strengthening religious values is a crucial strategy to enhance members’ saving decisions in Islamic microfinance institutions.